Recall-Net: A CNN-based Model for Four-class Classification of Alzheimer’s Disease - Hasan, M. M. Kamrul; Angan, Farhan Faisal; Rashid, Tasmim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.